Influence of therapeutic grip exercises induced loading rates in distal radius fracture healing with volar locking plate fixation. (March 2022) - Liu, Xuanchi; Miramini, Saeed; Patel, Minoo; Liao, JinJing; Shidid, Darpan; Zhang, Lihai
Highlights: Incorporate the dynamic behaviour of volar locking plate into fracture healing simulation. Consider the synergistic effect of biomechanical and biochemical stimuli on MSC differentiation. Physiologically dynamic loading benefits solute transport and chondrogenesis. Moderate loading frequency and fracture geometry promote indirect fracture healing. High loading frequency causes unfavourable fibroblast differentiation. Abstract: Background and objective: Therapeutic exercises could potentially enhance the healing of distal radius fractures (DRFs) treated with volar locking plate (VLP). However, the healing outcomes are highly dependant on the patient-specific fracture geometries (e.g., gap size) and the loading conditions at the fracture site (e.g., loading frequency) resulted from different types of therapeutic exercises. The purpose of this study is to investigate the effects of different loading frequencies induced by therapeutic exercises on the biomechanical microenvironment of the fracture site and the transport of cells and growth factors within the fracture callus, ultimately the healing outcomes. This is achieved through numerical modelling and mechanical testing. Methods: Five radius sawbones specimens (Pacific Research Laboratories, Vashon, USA) fixed with VLP (VRP2.0+, Austofix) were mechanically tested using dynamic test instrument (INSTRON E3000, Norwood, MA). The loading protocol used in mechanical testing involved a series of cyclic axial compression tests representing hand and finger therapeutic exercises. The relationship between the dynamic loading rate (i.e., loading frequency) and dynamic stiffness of the construct was established and used as inputs to a developed numerical model for studying the dynamic loading induced cells and growth factors in fracture site and biomechanical stimuli required for healing. Results: There is a strong positive linear relationship between the loading rate and axial stiffness of the construct fixed with VLP. The loading rates induced by the moderate frequencies (i.e., 1–2 Hz) could promote endochondral ossification, whereas relatively high loading frequencies (i.e., over 3 Hz) may hinder the healing outcomes or lead to non-union. In addition, a dynamic loading frequency of 2 Hz in combination of a fracture gap size of 3 mm could produce a better healing outcome by enhancing the transport of cells and growth factors at the fracture site in comparison to free diffusion (i.e. without loading), and thereby produces a biomechanical microenvironment which is favourable for healing. Conclusion: The experimentally validated numerical model presented in this study could potentially contribute to the design of effective patient-specific therapeutic exercises for better healing outcomes. Importantly, the model results demonstrate that therapeutic grip exercises induced dynamic loading could produce a better biomechanical microenvironment for healing without compromising the mechanical stability of the overall volar locking plate fixation construct.